Práticas colaborativas e interprofissionalidade na atenção básica à saúde de Sobral-Ceará. - Oliveira, Suelem Dias Monteiro (2024)
Interprofessional work in health, through collaborative practice, is presented as one of the best ways to face the highly complex challenges of the health sector, improving efficiency and quality of care, but it is associated with challenges such as routines, knowledge and identities different professionals, as well as professional hierarchies and time constraints. The Unified Health System (SUS) has comprehensiveness, equity and universality as its guiding principles, which are strong and structuring bases for the development of interprofessionality and collaborative practice. This study aimed to analyze collaborative practices and interprofessionality in Primary Health Care in Sobral, Ceará. This is an exploratory study, with a quantitative approach and cross-sectional design, with the participation of 281 professionals from the Family Health Strategy (ESF), Expanded Family Health Center (NASF) and the Multiprofessional Residency in Family Health (RMSF), from march to november 2023. The operationalization of the collection was carried out through the individual application of a socio-demographic questionnaire and the Interprofessional Team Collaboration Assessment Scale (AITCS II - BR). The collected data were organized in spreadsheets in Microsoft Excel® and SPSS 27.0 software, with analysis using the Mann-Whitney U and Kruskal-Wallis H tests. The study highlighted the existence of interprofessionality and collaborative practices, considering the dimensions: partnership, cooperation and shared decision-making and coordination. Regarding the factors associated with collaborative practice in PHC, the study showed that professionals trained in private institutions showed a greater tendency towards cooperation and shared decision-making and coordination compared to those trained in public institutions. It was also found that the positions of managers, doctors, nurses and nursing technicians have a higher level of cooperation and shared decision-making and that dentists, oral health technicians and community health agents have a lower level in this dimension. Another finding associated support from the RMSF or NASF with greater cooperation and shared decision-making in the ESF. In view of the findings of the study, there was a need to enhance interprofessional education actions in educational institutions, whether public or private, greater integration between the professionals who make up the ESF, especially the CHWs and oral health teams, and the importance the availability of multidisciplinary support in the ESF. Therefore, it was essential to invest in promoting interprofessionality and collaboration between health professionals to ensure more effective and comprehensive care for the population.